E-LEARNING: APPROPRIATE E-MATERIALS FORMATTING FOR USERS HEALTH - Mackare, Kristīne; Jansone, Anita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
E-learning has a direct relationship with public health as e-materials are making a huge amount of near workload for e-learners' eyes. As it is known, the huge near workload is one of the main reasons for the myopia development of nowadays population. The visual system can quickly become overloaded, especially by inappropriate e-material formatting. Based on theoretical research, incorrect formatting is used in most e-materials based on wrong recommendations. Recommendations and methodologies are not up-to-date for screen use. According to publications in the period of more than 20 years, near work and accommodation are the key factors for myopia development and progression. Appropriate formatting parameters of e-materials play an important role in reducing possible risk factors for myopia development. It could be achieved by using appropriate formatting parameters for e-learners. E-material font type must be perceptible and comprehensible from the screen, font size and line spacing must be appropriate for the reader based at least on its age and intellectual level, colour of background and text must help perception and reading process and could be different for each individual. All variables are important for individual and public health goals.  New recommendations and automatization of the formatting process are developed to reach improvement.